Disruption of the autism-associated gene SCN2A alters synaptic development and neuronal signaling in patient iPSC-glutamatergic neurons - Brown, Chad O.; Uy, Jarryll A.; Murtaza, Nadeem; Rosa, Elyse; Alfonso, Alexandria; Dave, Biren M.; Kilpatrick, Savannah; Cheng, Annie A.; White, Sean H.; Scherer, Stephen W.; Singh, Karun K. (Frontiers in Cellular Neuroscience, 2024)
SCN2A is an autism spectrum disorder (ASD) risk gene and encodes a voltage-gated sodium channel. However, the impact of ASD-associated SCN2A de novo variants on human neuron development is unknown. We studied SCN2A using isogenic SCN2A -/-induced pluripotent stem cells (iPSCs), and patient-derived iPSCs harboring a de novo R607* truncating variant. We used Neurogenin2 to generate excitatory (glutamatergic) neurons and found that SCN2A +/R607* and SCN2A -/-neurons displayed a reduction in synapse formation and excitatory synaptic activity. We found differential impact on actional potential dynamics and neuronal excitability that reveals a loss-of-function effect of the R607* variant. Our study reveals that a de novo truncating SCN2A variant impairs the development of human neuronal function.